Evaluation of the Adsorptive Potential of Zeolite Volcanic Tuff in Single and Binary Aqueous Solutions of the Basic Blue 41 Cationic Dye. Issue 14 (7th April 2022) - Ignat, Maurusa‐Elena; Dulman, Viorica; Ignat, Leonard; Ignat, Maria; Humelnicu, Ionel
Abstract: A volcanic tuff of clinoptilolite type has been assessed in regards to its efficiency on Basic Blue 41 (BB‐41) cationic dye removal from aqueous solutions. Optimal working conditions were established by considering influences of the particle sizes, initial pH, dye concentration, contact time, and temperature. Tuff samples have been characterized by using SEM/EDX, FT‐IR, and N2 gas adsorption‐desorption techniques. Experimental data at equilibrium showed a better fitting of adsorption kinetics on pseudo‐second‐order and Langmuir models, whereas the thermodynamic parameters indicate an endothermic spontaneous process. Tuff particles of 47 μm medium sizes, which own the highest zeolite content, were found to be the most suitable for practical use as adsorbents, attaining a maximum adsorptive capacity of 123.5 mg g −1 pure dye at 323 K, equivalent to 303 mg g −1 commercial product containing 40 % dye. A potential interference involving the retention pattern was furthermore evaluated within binary systems with other two cationic dyes, Rhodamine B (RhB) and Methylene Blue (MB). The adsorbent shows a relevant selectivity towards BB‐41, influenced by commercial dye additives, structural configuration, molecular size, and contact time, with the 99.7 % dye removal efficiency at 24 hours only slightly depressed in binary systems with RhB ‐ 97.4 %, respective MB ‐ 90.2 %. This study confirmed the tuff particles as efficient adsorbents for the treatment of textile wastewater effluents. Abstract : Clinoptilolite tuff is efficient and selective towards BB‐41 adsorption from single and mixed aqueous solutions, showing a dye removal efficiency of 99.7 % just slightly depressed in binary systems. Maximum adsorption capacity of 123.5 mg g −1 for pure BB‐41 dye was obtained at 323 K, mild acidic conditions and 47 μm medium sizes of tuff particles. Experimental data fits well with Langmuir and second‐pseudo‐order models, while thermodynamic modeling indicates an endothermic spontaneous process.